Impact of pain on cognitive functions in primary Sjögren syndrome with small fiber neuropathy: 10 cases and a literature review. Issue 16 (April 2017) - Indart, Sandrine; Hugon, Jacques; Guillausseau, Pierre Jean; Gilbert, Alice; Dumurgier, Julien; Paquet, Claire; Sène, Damien
Abstract : Abstract: Primary Sjögren syndrome (pSS) is a chronic systemic autoimmune disease characterized by xerophthalmia, xerostomia, and potential peripheral or central neurological involvement. In pSS, the prevalence of cognitive disorders is generally sparse across literature and the impact of pain on cognitive profile is unclear. The aim of this study was to determine the relation between pain, cognitive complaint, and impairment in a very homogenous population of 10 pSS patients with painful small fiber neuropathy (PSFN) and spontaneous cognitive complaint. Neurological exam, neuropsychological assessment, clinical evaluation measuring pain level, fatigue, anxiety, depression, and cognitive complaint were performed. Our results showed that 100% of patients had cognitive dysfunction especially in executive domain (80%). The most sensitive test was the Wisconsin Card Sorting Test (WCST), abnormal in 70% of our population. Moreover, we found clear cut significant correlations between pain levels and 3 measures of WCST: the number of errors ( R  = –0.768, P  = .0062), perseverations ( R  = 0.831, P  = .0042), and categories ( R  = 0.705, P  = .02). In the literature review, the impact of pain is underexplored and results could be discordant. In a homogeneous cohort of pSS patients with PSFN, a cognitive complaint seems to be a valid reflection of cognitive dysfunction marked by a specific executive profile found with the WCST. In this preliminary study, this profile is linked to the level of pain and highlights that an appropriate management of pain control and a cognitive readaptation in patients could improve the quality of life.